Antineutrophil cytoplasmic antibody-associated vasculitis with predominant truncal muscle weakness: a retrospective case series - Nemoto, Joe; Nishihara, Hideaki; Yasuhi, Taro; Sato, Ryota; Koga, Michiaki; Kanda, Takashi; Nakamori, Masayuki (Frontiers in Neurology, 2023)
Introduction: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) frequently leads to mononeuritis multiplex, which are characterized by distal weakness associated with sensory disturbances. Although AAV has also been reported to be associated with myopathy, the pathogenesis and characteristics remain unclear. We aimed to show the clinical and laboratory findings in AAV-associated myopathy.Methods: This retrospective single-center study included patients with the diagnosis of AAV who had been admitted to the neurology department and had biopsy specimens of muscle and/or nerve tissue. Results: We identified four patients with a distinct clinical presentation of muscle weakness in the trunk and proximal limbs. The weakness resembled that of inflammatory muscle disease. These patients denied symptoms associated with neuropathy, and had normal serum creatine kinase (CK) levels. Needle electromyography (needle EMG) showed spontaneous electrical activity at rest, and results of magnetic resonance imaging (MRI) suggested inflammatory myopathy.Muscle biopsy specimens from all four patients revealed vasculitis and inflammation in proximity to the affected vessels, without any discernible characteristics of other myopathies. The patients also complained of symptoms affecting other organs, such as the ears and kidneys, which is typical of AAV cases. Remission induction therapy, such as cyclophosphamide pulse therapy in addition to oral prednisolone, were effective for all four patients. However, relapses occurred in two patients during maintenance therapy and two patients died of aspiration pneumonia. Discussion: The clinical course of our patients might represent a subtype of AAV that is characterized by muscle weakness of the trunk and proximal extremities and arises from vasculitis within the muscles. The clinical manifestations of our patients were similar to those of patients with inflammatory myopathy with regard to the distribution of muscle weakness, MRI and needle EMG findings. However, there are notable differences between AAV associated myopathy versus inflammatory myositis like dermatomyositis; (1) the absence of elevated CK levels, (2) the presence of complications in other organs, (3) distinct pathological findings, and (4) severe outcomes. Awareness that AAV patients with muscle involvement could have a subtype of AAV that seriously affects various organs is critical for an accurate diagnosis and effective therapeutic management.